2022
DOI: 10.4085/1062-6050-625-21
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Education Balance Effects After Unilateral Rehabilitation in Individuals With Chronic Ankle Instability: A Systematic Review

Abstract: Objective To conduct a systematic review of existing literature of cross-education balance effects after unilateral training in the CAI population. Data Sources PubMed, SPORTDiscus, CINAHL Plus Study Selection To be included in the systematic review, studies were required to be published in English, include participants with chronic ankle instability, have pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…Moreover, hip strengthening in a cohort with CAI led to improved balance performance of the ipsilateral limb (10). In regard to previous evidence of cross-education effects in the CAI population, our current findings remain mostly incongruous with others that reported cross-education effects were achieved in this population (19). However, most studies reported contralateral improvements in balance performance only after a unilateral balance training protocol.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, hip strengthening in a cohort with CAI led to improved balance performance of the ipsilateral limb (10). In regard to previous evidence of cross-education effects in the CAI population, our current findings remain mostly incongruous with others that reported cross-education effects were achieved in this population (19). However, most studies reported contralateral improvements in balance performance only after a unilateral balance training protocol.…”
Section: Discussioncontrasting
confidence: 99%
“…To determine need, we encourage clinicians to complete bilateral assessments of outcomes, because impairments in those with CAI may occur unilaterally or bilaterally (11,12). Although unilateral balance training may alleviate bilateral impairments (19), we did not find that hip strength produced the same cross-education effects. Balance training and hip strengthening are established as effective interventions for CAI patients (10,31), although the value of lumbopelvic stabilization exercises in this population is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more studies are needed to differentiate such results from what is observed during the cross-education effect. This mechanism is very well described in the literature and may have influenced the results related to strength improvement and anabolic environment (29).…”
Section: Narrative Reviewmentioning
confidence: 85%
“…A possible explanation is that the balance intervention on the dominant lower limb favours it going further during the mSEBT when it is not the support lower limb. Another possible mechanism is the effect of cross-education, which is defined as adaptation of an untrained limb after unilateral training of the contralateral limb ( Son & Kang, 2020 ) and whose improvements appear to reflect use-dependent plasticity within the central nervous system ( i.e ., interhemispheric communication in the brain, primarily through the corpus callosum) ( Lawry-Popelka, Chung & McCann, 2022 ).…”
Section: Discussionmentioning
confidence: 99%